Simvastatin attenuates the c-Raf/Erk and calcineurin-NFATc2 pathways via inhibition of Hsp90 activity during the development of heart failure - Tetsuro Marunouchi; Kyo Fujita; Kirara Takahashi; Shunsuke Namiki; Lina Kyo; Manami Uchida; Emi Yano; Kouichi Tanonaka (Elsevier, 2023)
Hsp90 is a molecular chaperone that contributes to the activation and stabilization of client proteins. In our previous studies, we found that inhibition of Hsp90 delayed cardiac remodeling during the development of chronic heart failure in animal models. Simvastatin, an inhibitor of HMG-CoA reductase, has been shown to inhibit Hsp90. However, it is unclear whether simvastatin can prevent cardiac remodeling by inhibiting Hsp90. Therefore, the effects of simvastatin were examined in a rat model of chronic heart failure following myocardial infarction. The results showed that simvastatin reduced cardiac remodeling by inhibiting cardiac fibrosis. Furthermore, simvastatin decreased the expression of c-Raf and calcineurin, which are involved in intracellular signaling during the development of myocardial remodeling. In vitro, we found that the interaction of Hsp90 with c-Raf and calcineurin was reduced and the expression levels these client proteins were decreased in fibroblasts cultured in the presence of simvastatin. In addition, simvastatin also reduced proliferation, migration, and collagen production of fibroblasts. These results suggest that Hsp90 inhibition is partly responsible for the inhibitory effect of simvastatin on the development of myocardial remodeling.